STUDENTS’ WRITING NARRATIVE TEXT ABILITY BY USING LOCAL WISDOM BASED LEARNING MODEL - Gabby Maureen Pricilia; Habib Rahmansyah (Yayasan Literasi Kita Indonesia, 2021)
This study aim to determine the effect of using local wisdom based learning model on students’ writing narrative text ability at the fourth semester students of English Education Program in Institut Pendidikan Tapanuli Selatan. The research type is quantitative with experimental method. The researcher collected the data by using composition writing test. The sample was taken by using total sampling technique, it was 25 students. The data were then analyzed by using descriptive and inferential analysis, it was t-test formula by Arikunto. The results of the research are the mean score of students’ writing ability before using local wisdom based learning model was 53.54 which categorized bad, then after using local wisdom based learning model was 82.50 which categorized good. The hypothesis testing showed that t-test was higher than t-table, it means that the hypothesis is accepted. The finding of research reveals that there is a significant effect of local wisdom based learning model on students’ writing narrative text ability at the fourth semester students of English Education Program in Institut Pendidikan Tapanuli Selatan.